2005
DOI: 10.1103/physrevb.72.024305
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational entropy of spinodal decomposition in FeCr

Abstract: Inelastic neutron-scattering spectra were measured on stoichiometric Fe 0.50 Cr 0.50 prepared as a bodycentered-cubic ͑bcc͒ solid solution, and after increasing amounts of chemical unmixing on the bcc lattice induced by annealing the solid solution at 773 K. These spectra were reduced by a conventional procedure to a neutron-weighted vibrational density of states. Mössbauer spectrometry was used to characterize the extent of decomposition after annealing. A neutron-weight correction was performed, using result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…This observation is particularly interesting since recent studies have shown that besides thermal expansion effects, phonons often soften for other reasons such as electron-phonon coupling or internal structural rearrangements [17,[21][22][23]. Although phonon softening via electron-phonon coupling is likely to be dominant primarily in metals, such softening via changes in the structural rearrangements in the supercooled liquid state would be quite likely in glass-forming liquids.…”
Section: Resultsmentioning
confidence: 90%
“…This observation is particularly interesting since recent studies have shown that besides thermal expansion effects, phonons often soften for other reasons such as electron-phonon coupling or internal structural rearrangements [17,[21][22][23]. Although phonon softening via electron-phonon coupling is likely to be dominant primarily in metals, such softening via changes in the structural rearrangements in the supercooled liquid state would be quite likely in glass-forming liquids.…”
Section: Resultsmentioning
confidence: 90%
“…2) which are discussed in Ref. [28], none shows the features expected for phase-separated alloys [20][21][22][23][24][25][26][27]. In that case, P(B) would reveal a main peak due to the Fe-rich Fe-Cr bcc phase, centered at a field ranging Table 1 Average hyperfine magnetic fields and the associated standard deviations of the HMFDs of between ∼26 T (x = 0.25) and ∼27 T (x = 0.20) for T a ∼ 1200 • C according to the phase diagram proposed in Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Mössbauer studies of bcc Fe-Cr alloys ( [4,[20][21][22][23][24][25][26][27][28] and references therein) were and are still most often performed on as-cast alloys which are first cold-rolled, are then annealed for homogenization and to remove strain and are generally quenched. Various small angle neutron scattering experiments evidenced no signs of unmixing in alloys quenched in rather standard conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent computational study of the compositional trends in the NiCu system found the vibrational entropy of mixing to be negative, favoring chemical un-mixing [9]. Other phenomena in segregating systems where S vib is chief include the spinodal decomposition in FeCr [10] and the retrograde solubility in several dilute vanadium alloys [11]. Fe and Au are of major importance in industry and technology and the scientific literature on the Fe-Au system is vast, but bulk mixtures of Au and Fe atoms are largely immiscible at low temperatures.…”
Section: Introductionmentioning
confidence: 99%